Conditions de la parole pour des jeunes « harraga » en insertion à la Protection judiciaire de la jeunesse et impacts sur l’enseignement/apprentissage en français langue étrangère - Françoise Hickel (Sociétés et Jeunesses en Difficulté)
This article proceeds from a sociolinguistical and didactical research: “Multilingualism, mobility and language learning, from the complexity of language resources in context to their reflexive development in training”. This research was carried out in a collaborative approach within a Juvenile Justice training service. The attended public was mostly that of irregular Maghreb migrant youngsters. How one responds to the challenge of providing French as a foreign language training, when learners are unaccompanied minors, temporarily protected by Juvenile Justice, but in many ways vulnerabilized and far from being sure of a future in France?The article aims to show the central character of effecting contextualizations in order to think resources, needs and objectives of language training for those unaccompanied minors. A first contextualization axis focusses on the backgrounds and the departure motivations for those Maghreb young emigrants. A second contextualization axis introduces to the unaccompanied minors’ reception conditions in France, and their effects in discourse, and then points out paradoxes in which those young migrants are caught, by connecting their migration charateristics with constraints they have to cope with while staying in France. The article concludes on the way those migration and reception conditions lead to work on welcome modalities in the Juvenile Justice training service, to think about teaching/learning situations to be constructed, and to question the language training objectives, which cannot be defined solely from an integrative point of view.